Quandaries of contract cheating in South African higher education institutions: The way forward - Lubinga, S.; Ramnarain, J.; Tonkin, L. (South African Journal of Higher Education, 2023)
This research aimed to examine the quandaries of contract cheating faced by higher education institutions (HEIs) in South Africa. Based on a desktop study utilizing unobtrusive research methods such as documentary analysis and conceptual analysis of authoritative sources to conceptualise and provide context to contract cheating, the data drew secondary data from published journal articles. Findings demonstrated that the key quandaries of contract cheating are attributed to limited awareness of the concept, the undetectable nature of the action, the lack of law (lacuna) from the national point of view, gaps in existing institutional policies on misconduct, ambiguity in the conceptualisation, and expansion in the availability of this practice as evident in the increase use of custom essay websites, essay mills and file-sharing sites across the globe. To address these challenges, South African HEIs need to acknowledge that contract cheating is a problem which exists in institutions. Therefore, South African HEIs must revisit institutional policies on intellectual integrity and include a delineation of contract cheating, making a clear distinction between plagiarism and collusion. Additionally, South African HEIs must raise awareness of contract cheating amongst their students, invest in software that detects authenticity, such as Authorship Investigate, AI-Emma or Ouriginal, and design student-support-intervention marketing strategies to deter students from turning to contract cheating websites.